2019
DOI: 10.1021/acs.langmuir.9b02578
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Stöber Silica Nanoparticles with Controlled Moiety Densities Determines Their Cytotoxicity Profiles in Macrophages

Abstract: Physicochemical properties of nanomaterials play important roles in determining their toxicological profiles during nano-biointeraction. Among them, surface modification is one of the most effective manners to tune the cytotoxicity induced by nanomaterials. However, currently, there is no consistency in surface modification including moiety types and quantities considering the conflicting toxicological profiles of particles across different studies. In this study, in order to systematically investigate how the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 54 publications
2
26
0
Order By: Relevance
“…The exact mechanism of silica nanoparticleinduced cellular toxicity has not been elucidated. However, it is assumed that interaction of the silanol moiety of a particle surface with the cellular membrane and induction of ROS generation are involved [36,37]. Accordingly, we rst assessed intracellular ROS levels induced by silica-NPs using DCFDA, and found that amine modi cation of silica-NPs signi cantly attenuated intracellular ROS levels in RAW264.7 cells, which is concordant with previous observations [26] [35].…”
Section: Discussionsupporting
confidence: 88%
“…The exact mechanism of silica nanoparticleinduced cellular toxicity has not been elucidated. However, it is assumed that interaction of the silanol moiety of a particle surface with the cellular membrane and induction of ROS generation are involved [36,37]. Accordingly, we rst assessed intracellular ROS levels induced by silica-NPs using DCFDA, and found that amine modi cation of silica-NPs signi cantly attenuated intracellular ROS levels in RAW264.7 cells, which is concordant with previous observations [26] [35].…”
Section: Discussionsupporting
confidence: 88%
“…For example, Wang et al [126] reported that SiNPs increased LC3B expression in hepatocytes in a dose-and time-dependent manner, in accordance with the SiNP-induced cytotoxicity in hepatocytes. The study of Li, M., showed that the cytotoxicity of silica nanoparticles on macrophages was related to surface charge, and the cell survival rate increased with the surface modification of -COOH (negative charge), -NH 2 (positive charge), and polyethylene glycol (PEG, neutral) [127]. However, some researchers have discovered that MSNs have a positive effect on the cell viabilities of macrophages through inducing autophagy.…”
Section: Mesoporous Silica-based Nanomaterials (Msns)mentioning
confidence: 99%
“…To overcome this problem, cationic trimethylammonium (−NMe 3 + ) groups were incorporated into the cross-linked shell of micelles to promote colloidal stability in water, and amine moieties (−NH 2 ) were introduced for subsequent functionalization. 79,85 Uniform fiberlike micelles (L n = 412 nm, L w /L n = 1.19, Figures 5A and S10A) were first prepared via self-seeding in ethanol, followed by shell-cross-linking by the methods described above (Figure S3, see SI for details) to give uniform micelles with L n of 411 nm (L w /L n = 1.16). Then, (3aminopropyl)triethoxysilane (APTES, 25.4 μL, 0.11 mmol), along with trimethyl [3-(triethoxysilyl)propyl]ammonium chloride (TMTESA, 24.0 mg, 0.08 mmol), were added into micelle dispersion (0.05 mg/mL in ethanol, 12 mL).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We then attempted to induce in situ cross-linking of the PTESPMA layer of the micelles by siloxane condensation of TES moieties under mild acidic conditions. Uniform fiberlike micelles with a L n of 358 nm ( L w / L n = 1.18, Figure S6A) were used as a model for these shell-cross-linking reactions. An aqueous HCl solution (160 μL, 1.0 M) was added into the micelle dispersion (0.05 mg/mL in ethanol/THF with 0.5 vol % THF, 16 mL), followed by aging at 23 °C for 24 h. A relatively low micellar concentration (0.05 mg/mL) was used to prevent possible intermicellar cross-linking.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation